Studying the Swelling and Thermodynamic Functions of a Graft Co - polymer Using Different Molar Ratios of Acrylic Acid Monomer - F. Anad, Mazin; E. Salman , Hamieda; N. AL-Baiati, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
In this work, the graft co-polymer was prepared by using glycerol as material containing the three alcoholic groups that reacted with terphthalic acid, which has two carboxylic groups as a first step, and then 0.5 mole of fumaric acid was added to the prepared graft co-polymer as a second step. The acrylic acid monomer was added to the graft co-polymer in different numbers of moles (1.5, 2.0, & 2.5 mole). The swelling ratio measurements of the graft co-polymer in three different buffer solutions (2.2, 7.0, and 8.0) at the constant temperature of 310 K. The results showed that the increase in the number of moles of the acrylic acid monomer leads to an increase in the swelling ratio. Thermodynamic functions were calculated for the linear polymer.